(3fXe GdOQQ GdSfjI aj GdSjQ GdRcjIs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s
(3ChdgG (B:s
(3jbhd QGLj ef Edjg GdegQH YHOGdQMje Hf GdMSjf GdePfoH s
(3BNQgG (B:s
(3Ke Ydi YKeGf eY Ydqi hSGFQ GdCUMGH hGdhdqi s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B454 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B2127) s
Keywords: (3GdJGQjNs